Describing Interdisciplinary Agricultural Research Center Directors’ Perceptions of Science Communication Through Goals and Beliefs - Ashley McLeod-Morin; Ricky Telg; Joy Rumble (Journal of Applied Communications, 2020)
This study explored the perceptions of science communication held by interdisciplinary agricultural research center directors and identified the directors’ goals and beliefs, specifically related to science communication. Ten interdisciplinary agricultural research center directors from top research, land-grant institutions were interviewed for this study. Findings from this study determined that the directors’ perceptions were rooted in service to the public, knowledge, public good, obligation, and relationships. Participants discussed attempting to bring awareness to science as a goal of science communication. They also discussed feeling obligated to communicate about science as part of a land-grant institution. Participants particularly believed that faculty with Extension appointments were more so obligated to communicate with the public. Future research should determine the science communication participation of Extension faculty. Additionally, future research should determine if faculty at land-grant institutions are more inclined to communicate about science when compared to faculty not associated with land-grant institutions.
Keywords: science communication; qualitative; interdisciplinary science; Excellence Theory